2010
DOI: 10.1177/1524839909360171
|View full text |Cite
|
Sign up to set email alerts
|

Development, Theoretical Framework, and Lessons Learned From Implementation of a School-Based Influenza Vaccination Intervention

Abstract: The Advisory Committee on Immunization Practices (ACIP) recently recommended that all children 6 months to 18 years old be vaccinated annually against influenza. School-based influenza vaccination interventions may potentially increase influenza vaccination rates among hard-to-reach populations, particularly rural adolescents. This article describes the theoretical framework, intervention development, and lessons learned from 1st-year implementation of a multicomponent intervention aimed to promote influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…We have previously demonstrated that educational interventions targeting adolescents and their parents serve to improve uptake of influenza vaccine among adolescents (Gargano et al, 2011) and attitudes toward influenza vaccine in both parents and adolescents (Painter, Sales, Pazol, Grimes, et al, 2010; Painter, Sales, Pazol, Wingood, et al, 2010; Painter et al, 2011; Sales et al, 2011). Second, there are relatively few interventions described in the literature that apply health behavior theory to the fullest extent (Painter, Borba, Hynes, Mays, & Glanz, 2008; Painter, Sales, Pazol, Grimes, et al, 2010). Finally, to our knowledge, this study is the first to extensively engage middle- and high-school students through a science teacher-delivered curriculum to increase knowledge and positive attitudes toward all recommended adolescent vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that educational interventions targeting adolescents and their parents serve to improve uptake of influenza vaccine among adolescents (Gargano et al, 2011) and attitudes toward influenza vaccine in both parents and adolescents (Painter, Sales, Pazol, Grimes, et al, 2010; Painter, Sales, Pazol, Wingood, et al, 2010; Painter et al, 2011; Sales et al, 2011). Second, there are relatively few interventions described in the literature that apply health behavior theory to the fullest extent (Painter, Borba, Hynes, Mays, & Glanz, 2008; Painter, Sales, Pazol, Grimes, et al, 2010). Finally, to our knowledge, this study is the first to extensively engage middle- and high-school students through a science teacher-delivered curriculum to increase knowledge and positive attitudes toward all recommended adolescent vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…To date, teacher-delivered interventions have not been extensively utilized to impact vaccination behavior. Such interventions may be particularly important for increasing vaccine acceptance among adolescents (Painter, Sales, Pazol, Wingood, et al, 2010; Painter et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…39 The TDF has been used to design research studies such as improving hand hygiene compliance, 40 treatment pathways, 41, 42 forecasting health expectancy, 43 and improving the uptake of vaccination. 44, 45 …”
Section: Methodsmentioning
confidence: 99%
“…Painter et al developed a school-based educational program constructed from the HBM toward seasonal flu vaccination for a year, which led to a significant increase of vaccination rates among middle and high school students [16]. Durham et al investigated the effect of HBM variables on two protective behaviors toward influenza: vaccination and avoiding crowded places.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, OR 0 functions as a constant that defines the probability of the behavior when all x i variables are in their 'low' states[16]. For example for an individual in the control group with low perceived susceptibility (x 1 ¼ 0), high perceived severity (x 2 ¼ 1), high perceived benefit of vaccination (x 3 ¼ 1), high perceived barrier for vaccination (x 4 ¼ 1), the probability of vaccinating himself/herself against the flu is:…”
mentioning
confidence: 99%